The role of telemedicine in the management of patients with arterial hypertension and heart failure. - Kravchenko, Liubov Sergeevna; Zyyevedynova, Azada Arslanbekowna; Kolegova, Alexandra Nikitichna; Shikhshabekova, Elvira Ruslanovna; Dymova, Rusalina Aslanovna; Kiba, Maria Mikhailovna; Kornilova, Ksenia Alekseevna (Revista Latinoamericana de Hipertensión, 2025)
The article discusses the role of telemedicine I in the modern approach to the management I of patients with arterial hypertension (AH) and chronic heart failure (CHF). These diseases remain one of the main causes of disability and premature mortality worldwide, which requires the introduction of new technologies to improve the effectiveness of their management. Telemedicine technologies make it possible to remotely monitor patients' condition, ensure timely correction of treatment and improve compliance with therapeutic recommendations. The article analyses the benefits of using telemedicine, including the possibility of continuous monitoring of blood pressure, heart rate, body weight and other key parameters important for patients with AH and CHF. The importance of telemedicine platforms in improving the interaction between patients and medical specialists is emphasized, which helps to reduce the number of hospitalizations and complications. Particular attention is paid to the results of clinical trials demonstrating the positive impact of telemedicine programmes on blood pressure control and cardiac function. In addition, potential barriers to telemedicine implementation are discussed, such as technical limitations, economic factors and the need to adapt the health care system to new formats of work. The authors emphasise that telemedicine represents a promising direction in the management of chronic cardiovascular diseases, contributing not only to the improvement of patients' quality of life, but also to the optimization of healthcare costs. However, further standardization of telemedicine technology application methods and increased access to it among the general population are required to maximize its effectiveness.